2014
DOI: 10.1111/1753-0407.12173
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of prospective studies on the effects of nut consumption on hypertension and type 2 diabetes mellitus 对食用坚果对高血压和2型糖尿病的影响的前瞻性研究进行的meta分析

Abstract: Findings from this meta-analysis indicate that consumption of nuts (>2 servings/week) may be inversely associated with hypertension risk, but not with T2DM risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 49 publications
3
19
0
1
Order By: Relevance
“…Recently published pooled analyses of prospective studies on nut consumption mostly focused on CVDrelated morbidities and reported decreased risk of overall CVD, CAD, and hypertension (10)(11)(12)(13). On the contrary, nut consumption was not observed to significantly decrease stroke incidence (10), which was in line with our results on the association of stroke mortality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently published pooled analyses of prospective studies on nut consumption mostly focused on CVDrelated morbidities and reported decreased risk of overall CVD, CAD, and hypertension (10)(11)(12)(13). On the contrary, nut consumption was not observed to significantly decrease stroke incidence (10), which was in line with our results on the association of stroke mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Four recent meta-analyses showed that higher consumption of nuts was associated with reduced risk of coronary artery disease and hypertension (10)(11)(12)(13). However, pooled analyses that explored the effects of nut consumption on all-cause, CVD, and cancer mortality are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In observational studies, nuts lower CHD (196,212,213) and hypertension risk (213); but not stroke (207, (213). In one meta-analysis of prospective cohorts, nuts were not associated with T2DM (214), but in another, they were protective (207). Despite their high energy density, nuts do not contribute to weight gain, changes in waist circumference, or obesity perhaps owing to their satiating effects and increased fecal energy losses.…”
Section: Macronutrients Foods and Cvd Risk Factorsmentioning
confidence: 99%
“…国内 研究者完成的两项荟萃分析显示, 生活方式干预可使 糖尿病患者的血压标准化平均差分别降低0.19/0.08 [73] , 0.16/0.27 [74] . 另外两项荟萃分析则分别发现小檗碱可 降低血压5.97/2.69 mmHg [75] 、每周进食2次以上坚果 可降低高血压风险8% [76] . 高盐摄入是高血压的主要危 险因素, 糖尿病合并高血压存在盐敏感性增加, 实验研 究显示肥胖合并糖尿病的db/db小鼠(Mus musculus)予 高盐后, 明显升高血压, 其PPARδ/脂联素/SGLT-2介导…”
Section: 国内研究者进行的荟萃分析则显示Dpp-4抑制剂有更unclassified